2015
DOI: 10.1021/acsami.5b01641
|View full text |Cite
|
Sign up to set email alerts
|

Co-electroplated Kesterite Bifacial Thin-Film Solar Cells: A Study of Sulfurization Temperature

Abstract: Earth-abundant material, kesterite Cu2ZnSnS4 (CZTS), demonstrates the tremendous potential to serve as the absorber layer for the bifacial thin-film solar cell. The exploration of appropriate sulfurization conditions including annealing temperature is significant to gain insight into the growth mechanism based on the substrates using transparent conductive oxides (TCO) and improve device performance. The kesterite solar absorbers were fabricated on ITO substrates by sulfurizing co-electroplated Cu-Zn-Sn-S prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 64 publications
6
30
1
Order By: Relevance
“…A bifacial thin-film photovoltaic using CIGS on TCO was first investigated by Nakada et al, 7 and the concept was later applied to CIGS and CZTSSe solar cells. [8][9][10][11][12][13] Another added benefit of the bifacial design is the ability to utilize these semi-transparent thin-film solar cells in other devices such as tandem solar cells and solar windows. 14 Accordingly, bifacial CZTSSe solar cells using TCO back contacts such as indium tin oxide (ITO), aluminum-doped zinc oxide (AZO), and fluorine-doped tin oxide (FTO) have been studied by many research groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A bifacial thin-film photovoltaic using CIGS on TCO was first investigated by Nakada et al, 7 and the concept was later applied to CIGS and CZTSSe solar cells. [8][9][10][11][12][13] Another added benefit of the bifacial design is the ability to utilize these semi-transparent thin-film solar cells in other devices such as tandem solar cells and solar windows. 14 Accordingly, bifacial CZTSSe solar cells using TCO back contacts such as indium tin oxide (ITO), aluminum-doped zinc oxide (AZO), and fluorine-doped tin oxide (FTO) have been studied by many research groups.…”
mentioning
confidence: 99%
“…14 Accordingly, bifacial CZTSSe solar cells using TCO back contacts such as indium tin oxide (ITO), aluminum-doped zinc oxide (AZO), and fluorine-doped tin oxide (FTO) have been studied by many research groups. [10][11][12][13] To date, most reports regarding bifacial CZTSSe were based on solution processing methods. For example, Ge et al reported Cu 2 ZnSnS 4 (CZTS) solar cells prepared through co-electroplating on an ITO substrate, which exhibited only 3.4% conversion efficiency under bifacial illumination.…”
mentioning
confidence: 99%
“…The relatively high EQE result of CZTS_Citrate is consistent with the higher Jsc of this device compared to CZTS_Pyro. However, the highest value in the EQE curves are much lower than the reported values [187,190].…”
Section: Electrical and Optical Properties Of Czts Based Solar Ccontrasting
confidence: 58%
“…The most common annealing or sulfurization temperature range is between 500 and 600 °C for CZTS based devices, where large, uniform crystal grains are obtained [125,[141][142][143].…”
Section: Influence Of Sulfurization Temperature On the Pec Performentioning
confidence: 99%
See 1 more Smart Citation